Efficacy of Virtual Reality and Exergaming in Improving Balance in Patients With Multiple Sclerosis: A Systematic Review and Meta-Analysis - Calafiore, Dario; Invernizzi, Marco; Ammendolia, Antonio; Marotta, Nicola; Fortunato, Francesco; Paolucci, Teresa; Ferraro, Francesco; Curci, Claudio; Cwirlej-Sozanska, Agnieszka; de Sire, Alessandro (Frontiers in Neurology, 2021)
Multiple sclerosis (MS) is one of the most common causes of neurological progressive disease and can lead to loss of mobility, walk impairment and balance disturbance. Several rehabilitative approaches have been proposed and, in recent years, exergaming and virtual reality have been studied in both rehabilitative clinical and research setting. Active video game therapy could reduce the boredom of the rehabilitation process, increasing patient motivation, providing direct feedback and enabling dual-task training. Therefore, the purpose of this study is to assess the effectiveness of exergaming and virtual reality for balance recovery in MS patients. PubMed, Scopus, Web of Science were systematically searched from the inception until May 14th, 2021, to identify randomized controlled trials (RCTs) presenting: MS patients as participants; Exergaming/VR as intervention; conventional rehabilitation as comparator; balance assessment (Berg Balance Scale - BBS), as outcome measure. We also performed a meta-analysis of the mean difference in BBS via the random effect method. Out of 93 records, 7 RCTs were analyzed in this systematic review. The 7 studies have been published in the last 7 years (from 2003 to 2020) and included a total of 209 patients affected by MS, of which 97 performed exergaming or virtual reality and 112 underwent conventional rehabilitation. A pairwise meta-analysis reported a significant effect size of VR in terms of BBS improvement, whereas exergaming did not provide any significant BBS effect size modification. Taken together, these findings suggested that balance rehabilitation using exergames and virtual reality appears to be more effective than conventional rehabilitation in patients affected by MS.